Perilaku keputusan investasi investor pasar saham Indonesia - Lim, Rico Limgestu; Yulfis; Alvin; Nopry; Ilianto Tri Sagianto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study is to examine the investment decision-making behavior of Indonesian retail investors. Investors make investment decisions based on a set of priorities. The need to understand stock market investment decision behavior goes beyond the movable owner to have a good understanding of their experience, the type of information sought before making an investment decision, potential elements that lead to poor investment decisions, challenges faced during investment. This research utilizes purposive sampling technique and qualitative research methodology, with a sample of Indonesian stock market investors domiciled in Batam. The research findings show that Batam city investors make decisions based on convenience or convention rather than quantitative analysis, and they rely heavily on their findings, company performance and the impact of currency exchange rates, which are based on Experience overcoming challenges.